Time course and mechanisms of left ventricular systolic and diastolic dysfunction in monocrotaline-induced pulmonary hypertension - Correia-Pinto, Jorge (2009)
Although pulmonary hypertension (PH) selectively overloads the right ventricle (RV), neuroendocrine activation and intrinsic myocardial dysfunction have been described in the left ventricle (LV). In order to establish the timing of LV dysfunction development in PH and to clarify underlying molecular changes, Wistar rats were studied 4 and 6 weeks after subcutaneous injection of monocrotaline (MCT) 60 mg/kg (MCT-4, n = 11; MCT-6, n = 11) or vehicle (Ctrl-4, n = 11; Ctrl-6, n = 11). Acute single beat stepwise increases of systolic pressure were performed from baseline to isovolumetric (LVPiso). This hemodynamic stress was used to detect early changes in LV performance. Neurohumoral activation was evaluated by measuring angiotensin-converting enzyme (ACE) and endothelin-1 (ET-1) LV mRNA levels. Cardiomyocyte apoptosis was evaluated by TUNEL assay. Extracellular matrix composition was evaluated by tenascin-C mRNA levels and interstitial collagen content. Myosin heavy chain (MHC) composition of the LV was studied by protein quantification. MCT treatment increased RV pressures and RV/LV weight ratio, without changing LV end-diastolic pressures or dimensions. Baseline LV dysfunction were present only in MCT-6 rats. Afterload elevations prolonged tau and upward-shifted end-diastolic pressure dimension relations in MCT-4 and even more in MCT-6. MHC-isoform switch, ACE upregulation and cardiomyocyte apoptosis were present in both MCT groups. Rats with severe PH develop LV dysfunction associated with ET-1 and tenascin-C overexpression. Diastolic dysfunction, however, could be elicited at earlier stages in response to hemodynamic stress, when only LV molecular changes, such as MHC isoform switch, ACE upregulation, and myocardial apoptosis were present.